Effects of combining inducible nitric oxide synthase inhibitor and radical scavenger during porcine bacteremia - Matejovic, Martin; Krouzecky, Ales; Rokyta, Richard; Radej, Jaroslav; Kralova, Hana; Treska, Vladislav; Radermacher, Peter; Novak, Ivan (Shock (Augusta, Ga.), 2007)
Complex interactions of nitric oxide and other free radicals have been implicated in the pathogenesis of sepsis and organ dysfunction. We hypothesized that simultaneous inducible nitric oxide synthase inhibition (L-N6-[1-iminoethyl]-lysine [L-NIL]) and neutralization of superoxide (O2-) (4-hydroxy-2,2,6,6-tetramethylpiperidine-N-oxyl [Tempol]) would protect from detrimental consequences of long-term, volume-resuscitated, hyperdynamic porcine bacteremia. In this prospective, randomized, controlled experimental study, 16 anesthetized, mechanically ventilated and instrumented pigs were exposed to 24 h of continuous infusion of live Pseudomonas aeruginosa. After 12 h of hyperdynamic sepsis, animals were randomized to receive either vehicle (control, n = 8) or combination of L-NIL and Tempol (n = 8). Systemic and hepatosplanchnic hemodynamics, oxygen exchange, metabolism, ileal mucosal microcirculation and tonometry, oxidative stress and coagulation parameters were assessed before, 12, 18, and 24 h of P. aeruginosa infusion. Combined treatment inhibited sepsis-induced increase in plasma nitrate/nitrite, 8-isoprostane, and thiobarbituric acid reactive species concentrations, prevented hypotension, and reversed hyperdynamic circulation. Despite lower intestinal macrocirculation, combined regimen attenuated the otherwise progressive deterioration in ileal mucosal microcirculation and prevented mucosal acidosis. Treatment substantially attenuated mesenteric and hepatic venous acidosis, preserved sepsis-induced impairment of hepatosplanchnic redox state, and prevented the development of renal dysfunction. Finally, coinfusion of L-NIL and Tempol largely attenuated the sepsis-induced rise in plasma von Willebrand factor and thrombin-antithrombin complexes. Thus, hemodynamic, microcirculatory, metabolic, renal, and coagulation data indicate that combining inducible inhibition with cell permeable O2(-) radical scavenger afforded significant protection in porcine sepsis, thus suggesting an important interactive role of O2(-) and nitric oxide in mediating organ dysfunction.
Keywords: Nitric Oxide Synthase Type II; Spin Labels; Animals; bakteriemie; Bacteremia; Pseudomonas Infections; synthasa oxidu dusnatého, typ II; Free Radical Scavengers; pseudomonádové infekce; zvířata; scavengery volných radikálů; cyklické N-oxidy; prasata; Swine; Pseudomonas aeruginosa; spinové značení; Cyclic N-Oxides